Does perceived technology and knowledge of maintenance influence purchase intention of BEVs. (April 2021) - Pradeep, Viyaluru Harinath; Amshala, Vijay Teja; Raghuram Kadali, B
Highlights: This study analyses battery electric vehicle adoption in Indian context. The consumer attitude is a strong predictor in purchase intention of BEV. Knowledge of maintenance had indirect effects on purchase intention of BEV Perceived technology had a direct and indirect impact on purchase intention of BEV. Instrumental attributes were found to act as barriers against the adoption of BEV. Abstract: Electric vehicles have been widely regarded as an alternative to conventional combustion fuel vehicles in reducing traffic emissions. In this study, an extended theory of planned behaviour has been proposed to study the factors that influence the adoption of battery electric vehicles in Indian context. Analysis has been performed using factor-based regression technique and results revealed that attitude is found to be the strongest predictor. Moreover, the impact of knowledge of maintenance and perceived technology was explored on purchase intention of Battery Electric Vehicle (BEV). Also, a mediation analysis has been performed to determine its significance. Results revealed that knowledge of maintenance did not have any direct effects, but showed significant indirect effects, whereas the perceived technology had a pronounced impact with significant direct and indirect effects on purchase intentions. Further, these results are beneficial to policymakers and transport planners in motivating the urban commuters towards a more sustainable transport mode.